Profiles of parents’ emotion socialization within a multinational sample of parents - King, Gabriella L.; Macdonald, Jacqui A.; Greenwood, Christopher J.; Kehoe, Christiane; Dunsmore, Julie C.; Havighurst, Sophie S.; Youssef, George J.; Berkowitz, Tomer S.; Westrupp, Elizabeth M. (Frontiers in Psychology, 2023)
Introduction Seminal emotion socialization theories classify parents according to two patterns of parent emotion socialization processes: ‘emotion coaching’ (i.e., parents validate and teach children about emotions) versus ‘emotion dismissing’ parenting (i.e., parents minimize and dismiss their children’s emotions). However, empirical evidence supporting this binary distinction of parents remains limited. Our objective was to investigate whether parents can be differentiated by distinct patterns in their (1) beliefs about children’s emotions, (2) emotion regulation, and (3) emotion-related parenting practices. Method Participants were parents of children aged 4–10 years from the Child and Parent Emotion Study (N = 869) (https://bmjopen.bmj.com/content/10/10/e038124). Parents completed self-reported measures of emotion socialization processes via an online survey, which took 20–30 min to complete. Data included in the current study were collected May–August 2019. We conducted a latent profile analysis of parents’ emotion socialization (13 indicators). To assess reliability of the profiles, we examined stability of the profiles across (1) parents of children in early versus middle childhood, and (2) fathers versus mothers, via measurement invariance testing. Further, to assess for construct validity of the profiles, we examined concurrent associations between six criterion constructs and parents’ emotion socialization profiles. Results A three-profile model emerged characterizing parents by: (1) emotion coaching; (2) emotion dismissing; (3) emotion disengaged. There was strong support for construct validity and reliability. Discussion Our study provides empirical support for distinct differentiated classifications of emotion coaching and emotion dismissing parenting, aligned with emotion socialization theories. We further extend on extant theory and suggest a third ‘emotion disengaged’ classification, describing parents with moderate levels of emotion dismissing parenting and low levels of emotion coaching parenting. It should be noted that the profiles were derived with self-report data, therefore, data may have been biased by contextual factors. Furthermore, the study sample consisted of Western families from affluent backgrounds. The field should focus efforts on conducting person-centered studies with more diverse samples in future.